2023
DOI: 10.14744/tjtes.2022.02362
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between the presence of scapula fracture and mortality and morbidity in cases with blunt thoracic trauma

Abstract: BACKGROUND: Scapula fractures (SFs) occur as a result of high-energy trauma and are significant in terms of life-threatening injuries. There are few studies showing the relationship between SFs and mortality and morbidity in patients with blunt thoracic trauma (BTT). Our study aims to investigate the relationship between SF and mortality and morbidity in BTT. METHODS:Adult patients admitted to the emergency department of Kahramanmaras Sutcu Imam University, School of Medicine with BTT between January 2019 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 16 publications
3
11
0
Order By: Relevance
“…In agreement with other studies, scapular fracture was significantly associated with thoracic injuries such as multiple rib fractures and pneumothorax [ 1 , 2 , 4 ] ( Table 3 ). A retrospective study over 6 years conducted in the United Kingdom showed that there was no significant difference regarding lung contusion between patients with scapular fractures and patients without fractures [ 18 ].…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In agreement with other studies, scapular fracture was significantly associated with thoracic injuries such as multiple rib fractures and pneumothorax [ 1 , 2 , 4 ] ( Table 3 ). A retrospective study over 6 years conducted in the United Kingdom showed that there was no significant difference regarding lung contusion between patients with scapular fractures and patients without fractures [ 18 ].…”
Section: Discussionsupporting
confidence: 92%
“…Injury severity parameters such as ISS, NIS, and ICU admission were significantly higher in patients with scapular fracture compared to other patients without fracture, which is similar to other studies [ 1 , 4 , 18 ]. Accordingly, as expected, the length of hospital stay was significantly longer in patients with scapular fracture patients who had more severe injuries.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations